Harassment through Digital Media: A Cross-Jurisdictional Comparative Analysis on the Law on Cyberstalking - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2007)
The cyber world is an extension of the real world. It is another dimension where we can work, study and play. But people also tend to lose their inhibitions on the Internet, often while keeping their anonymity. Because of the perceived and real freedoms in the digital environment, people are emboldened to act in ways that they may not normally do in the real world. One recent phenomenon that is steadily becoming a problem in every country with a high level of electronic connectivity is the act of cyberstalking. The electronic medium is significant due to its very nature such as low cost and ease of use, potential anonymity and stealth as well as the insignificance of physical distance to the act of stalking. Hence, cyberspace affords lesser impediments to aggressive behaviour. The borderless nature of electronic communications medium, concomitant jurisdictional concerns and the unique challenges posed to computer forensics such as the collection of evidence and investigations also arise as relevant issues in this context. Cyberstalking has become a concern that has translated into law in larger jurisdictions such as the United States, the United Kingdom, Canada, Australia, Japan and even in a small country like Singapore. Existing laws relating to harassment or intimidation are fact- or relationship- specific and are inadequate to meet the needs of modern society, while nascent cyberstalking laws are substantively disparate. I will analyse and compare the cyberstalking laws of several key jurisdictions to determine the common elements and treatment and to come up with a proposed statutory solution that will take into consideration the different rights and interests of members of society in the use of digital media for social interaction. I will also briefly consider the issues of prescriptive, adjudicatory and enforcement jurisdiction in support of greater international cooperation to deal with the problem through the harmonisation of substantive laws, the coordination in procedural investigative measures and complementary recognition and enforcement laws.